197k views
16 votes
Plz help I don’t understand how to do this problem

Plz help I don’t understand how to do this problem-example-1
User Kathi
by
4.7k points

1 Answer

5 votes

Answer:

  • a) 6
  • b) 3t² - 17t + 28
  • c) 3t² - 5t - 2

Explanation:

Given function:

  • g(t) = 3t² - 5t + 4

a) g(2)

  • g(2) = 3*2² - 5*2 + 4 =
  • 3*4 - 10 + 4 =
  • 12 - 6 =
  • 6

b) g(t - 2)

  • g(t - 2) = 3(t - 2)² - 5(t - 2) + 4 =
  • 3(t² - 4t + 4) - 5t + 10 + 4 =
  • 3t² - 12t + 12 - 5t + 16 =
  • 3t² - 17t + 28

c) g(t) - g(2)

  • g(t) - g(2) = 3t² - 5t + 4 - 6 =
  • 3t² - 5t - 2
User Jose Rocha
by
4.8k points